Istota i funkcje ubezpieczenia chorobowego rolników - Puślecki, Damian (Wydawnictwo Naukowe UAM, 2012)
The aim of the paper was to determine the essence and function of the farmers’ social insurance against sickness, by looking at the insured object, that is the capability of the insured farmer to earn his living by the work of his hands. When assessing the insurance cover available to individuals involved in an agricultural activity, one should take into account not only the risk of a farmer falling ill, that is the sickness risk, but, first of all, the quality of the benefits paid in the event of sickness. The paper concludes with a statement that the currently binding regulation in Polish law is not adequate and does not satisfy the needs of those engaged in agricultural activity. Sickness insurance must be treated separately in the Insurance Act, the sickness insurance premiums paid by the farmers must be recalculated, and the amounts of insurance benefits paid to the insured must be increased. A higher sickness benefit would not only partially compensate an insured farmer for the lost earnings, but would also provide a real opportunity allowing the insured person to maintain the continuity of agricultural production. The sickness insurance should combine the protecting, guaranteeing, compensating-supporting and a preventive function.

Lo scopo dell’articolo è di determinare la natura e le funzioni dell’assicurazione malattie degli agricoltori. La loro analisi è stata effettuata attraverso il prisma dell’oggetto della copertura dell’assicurazione, ossia della capacità dell’assicurato di garantirsi adeguati mezzi di sussistenza eseguendo il proprio lavoro. Nel valutare la portata della copertura dovuta alle persone che svolgono attività agricola, bisogna tener conto non solo del rischio di malattie presenti in agricoltura, ma soprattutto della questione della qualità delle retribuzioni. Concludendo, l’autore afferma che la concezione di assicurazione malattie attualmente assunta non trova una giustificazione nell’attività agricola. Vi è una evidente necessità di distinguere l’assicurazione malattie nella legge sulle assicurazioni, di effettuare un nuovo calcolo dei contributi versati dagli agricoltori per l’assicurazione malattie e di aumentare categoricamente l’importo delle retribuzioni corrisposte. L’aumento dell’importo dell’indennità di malattia non solo consentirebbe una parziale compensazione del reddito perso, ma anche una reale possibilità di mantenere la continuità della produzione agricola. La portata della copertura prevista dalle norme della legge sull’assicurazione a favore dell’agricoltore è troppo ridotta. Essa dovrebbe riflettersi nelle funzioni dell’assicurazione malattie: protezione, garanzia, compensazione-sostegno e anche prevenzione.